THE APPLICATION OF PROBLEM BASED LEARNING TO INCREASE CRITICAL THINKING AND METACOGNITIVE GRADE XII STUDENTS AT SENIOR HIGH SCHOOL (SMA) “XYZ” MAKASAR - Hildegardis Retno Harsanti; . Khaterine; Niko Sudibjo (Bandar Lampung University (UBL), 2016)
Traditional learning, where a teacher teaches in a classroom and the students only listen, has several weaknesses. Some of the weaknesses are students have the tendency to be passive and less critical in the process of teaching and learning. The objective of this research is to analyze the effect of applying the problem based learning to students’ critical thinking and metacognitive. This research was conducted using quantitative approach and experiment method. The subjects of this research were 28 grade XII students at High School